Celastrol mitigates inflammation in sepsis by inhibiting the PKM2-dependent Warburg effect - Piao Luo; Qian Zhang; Tian-Yu Zhong; Jia-Yun Chen; Jun-Zhe Zhang; Ya Tian; Liu-Hai Zheng; Fan Yang; Ling-Yun Dai; Chang Zou; Zhi-Jie Li; Jing-Hua Liu; et al. (Military Medical Research, 2022)
Abstract Background Sepsis involves life-threatening organ dysfunction and is caused by a dysregulated host response to infection. No specific therapies against sepsis have been reported. Celastrol (Cel) is a natural anti-inflammatory compound that shows potential against systemic inflammatory diseases. This study aimed to investigate the pharmacological activity and molecular mechanism of Cel in models of endotoxemia and sepsis. Methods We evaluated the anti-inflammatory efficacy of Cel against endotoxemia and sepsis in mice and macrophage cultures treated with lipopolysaccharide (LPS). We screened for potential protein targets of Cel using activity-based protein profiling (ABPP). Potential targets were validated using biophysical methods such as cellular thermal shift assays (CETSA) and surface plasmon resonance (SPR). Residues involved in Cel binding to target proteins were identified through point mutagenesis, and the functional effects of such binding were explored through gene knockdown. Results Cel protected mice from lethal endotoxemia and improved their survival with sepsis, and it significantly decreased the levels of pro-inflammatory cytokines in mice and macrophages treated with LPS (P < 0.05). Cel bound to Cys424 of pyruvate kinase M2 (PKM2), inhibiting the enzyme and thereby suppressing aerobic glycolysis (Warburg effect). Cel also bound to Cys106 in high mobility group box 1 (HMGB1) protein, reducing the secretion of inflammatory cytokine interleukin (IL)-1β. Cel bound to the Cys residues in lactate dehydrogenase A (LDHA). Conclusion Cel inhibits inflammation and the Warburg effect in sepsis via targeting PKM2 and HMGB1 protein.